Constraint Guided Beta-Sheet Refinement for Protein Structure Prediction. (December 2022) - Newton, M.A. Hakim; Zaman, Rianon; Mataeimoghadam, Fereshteh; Rahman, Julia; Sattar, Abdul
Abstract: Protein structure prediction (PSP) is a crucial issue in Bioinformatics. PSP has its important use in many vital research areas that include drug discovery. One of the important intermediate steps in PSP is predicting a protein's beta-sheet structures. Because of non-local interactions among numerous irregular areas in beta-sheets, their highly accurate prediction is challenging. The challenge is compounded when a given protein's structure has a large number of beta-sheets. In this paper, we specifically refine the beta-sheets of a protein structure by using a local search method. Then, we use another local search method to refine the full structure. Our search methods analyse residue–residue distance-based scores and apply geometric restrictions gained from deep learning models. Moreover, our search methods recognise the regions of the current conformations prompting the nether scores and generate neighbouring conformations focusing on that identified regions and making alterations there. On a set of standard 88 proteins of various sizes between 46 and 450 residues, our method successfully outperforms state-of-the-art PSP search algorithms. The improvements are more than 12% in average root mean squared distance (RMSD), template modelling score (TM-score), and global distance test (GDT) values. Graphical abstract: